Trust and the regulation of pharmaceuticals: South Asia in a globalised world - Rawal Nabin; Jeffery Roger; Harper Ian; Brhlikova Petra; Subedi Madhusudhan; Santhosh MR (BMC, 2011)
Abstract Background Building appropriate levels of trust in pharmaceuticals is a painstaking and challenging task, involving participants from different spheres of life, including producers, distributors, retailers, prescribers, patients and the mass media. Increasingly, however, trust is not just a national matter, but involves cross-border flows of knowledge, threats and promises. Methods Data for this paper comes from the project 'Tracing Pharmaceuticals in South Asia', which used ethnographic fieldwork and qualitative interviews to compared the trajectories of three pharmaceuticals (Rifampicin, Oxytocin and Fluoxetine) from producer to patient in three sites (north India, West Bengal and Nepal) between 2005-08. Results We argue that issues of trust are crucial in reducing the likelihood of appropriate use of medicines. Unlike earlier discussions of trust, we suggest that trust contexts beyond the patient-practitioner relationship are important. We illustrate these arguments through three case studies: (i) a conflict over ethics in Nepal, involving a suggested revised ethical code for retailers, medical representatives, producers and prescribers; (ii) disputes over counterfeit, fake, substandard and spurious medicines, and quality standards in Indian generic companies, looking particularly at the role played by the US FDA; and (iii) the implications of lack of trust in the DOTS programmes in India and Nepal for the relationships among patients, government and the private sector. Conclusions We conclude that the building of trust is a necessary but always vulnerable and contingent process. While it might be desirable to outline steps that can be taken to build trust, the range of conflicting interests in the pharmaceutical field make feasible solutions hard to implement.